KEKUATAN YANG MEMBISU (SEBUAH PENGAKUAN) - Lia Amelia (Jurnal Seni Makalangan, 2014)
Kekuatan Diam (A Confession) adalah karya tari yang disajikan dalam bentuk tarian yang dramatis. Karya ini terinspirasi oleh fenomena sosial berdasarkan pengalaman pribadi penyaji pada posisi seorang perempuan. Seorang perempuan memiliki kekuatan tersembunyi yang tidak dimiliki oleh laki-laki, perempuan ingin dihormati, perempuan melahirkan anak-anak yang akan menjadi generasi penerus. Fitrah perempuan di antaranya: hamil, melahirkan, menyusui, mengurus rumah tangga, dan lain-lain. Seiring perkembangan zaman, banyak perempuan yang berkarier, bekerja di luar rumah, tapi mereka menyadari bahwa mengurus rumah tangga harus diprioritaskan.Kata kunci: Dramatis, Kekuatan, Wanita, Makna.AbstrakThe strength of silence (A Confession) is a dance work presented in the form of dramatic dance.   This work was inspired by a social phenomenon based on performer’s experience as a woman. A woman has a hidden power which is not owned by a man, a woman wants to be honored, a woman gives birth to children who will be the next generation. The nature of a woman among others: pregnant, giving birth, breastfeeding, housekeeping, etc. Along the times, there are many women who become career women and work out, but they still realize that taking care of the household should be prioritized. Keywords: Dramatic, Strength, Woman, Meaning.